Simple Engineering-Based Cardboard Game Media to Support Contextual Learning at Al-Ya'lu Elementary School, Malang. - Maulana, Jibril; Riyanto, Obaja Eden Sentosa; Sasongko, Muhammad Ilman Nur; Andrianto, Sis Nanda Kus; Lubis, Didin Zakariya (Yayasan Lentera Avanya Nagari, 2025)
Educational games have been widely recognized as effective instructional tools that enhance students’ motivation and engagement in learning. This community engagement program aims to strengthen contextual learning for fourth- and fifth-grade students at SD Unggulan Al-Ya’lu through the development and implementation of simple engineering-based cardboard game media. The initiative addresses the school’s demand for practical and engaging teaching aids that connect abstract scientific concepts—such as force, motion, and simple mechanisms—with real-world phenomena. A problem-solving approach was employed, consisting of four key phases: preparation, program socialization, counseling, and hands-on training. During the implementation, students were guided to design and construct low-cost educational games made from recycled cardboard, including hydraulic claw machines and simple vending machines. The impact of the program was evaluated through pre-test and post-test assessments to measure students’ conceptual understanding. The results indicated a significant improvement in comprehension scores, increasing from an average of 64.36 to 87.05. This outcome reflects enhanced cognitive skills and a deeper understanding of basic mechanical concepts. Furthermore, the activity fostered collaboration, creativity, and active participation. These findings demonstrate that simple, low-cost engineering projects can serve as effective contextual learning media and provide sustainable pedagogical strategies for elementary education. Permainan edukatif telah terbukti dapat digunakan sebagai media pembelajaran yang efektif dalam meningkatkan motivasi dan keterlibatan peserta didik. Program pengabdian masyarakat ini bertujuan untuk memperkuat pembelajaran kontekstual bagi siswa kelas IV dan V di SD Unggulan Al-Ya’lu melalui pengembangan dan penerapan media permainan kardus berbasis rekayasa sederhana. Inisiatif ini dilatarbelakangi oleh kebutuhan sekolah terhadap media pembelajaran yang praktis dan menarik guna menjembatani konsep-konsep sains dasar—seperti gaya, gerak, dan mekanisme sederhana—dengan fenomena nyata di lingkungan sekitar. Pendekatan pemecahan masalah digunakan melalui empat tahapan utama, yaitu persiapan, sosialisasi program, penyuluhan, dan pelatihan praktik. Dalam pelaksanaannya, siswa dilatih untuk merancang dan membuat permainan edukatif berbiaya rendah dari kardus bekas, seperti mesin capit hidrolik dan mesin penjual sederhana. Dampak kegiatan dievaluasi melalui pre-test dan post-test untuk mengukur peningkatan pemahaman konsep siswa. Hasil menunjukkan peningkatan signifikan dari skor rata-rata 64,36 menjadi 87,05, yang mencerminkan peningkatan kemampuan kognitif dan pemahaman terhadap konsep mekanika dasar. Selain itu, kegiatan ini juga mendorong kolaborasi, kreativitas, serta partisipasi aktif siswa. Temuan ini menegaskan bahwa proyek rekayasa sederhana berbiaya rendah dapat menjadi media pembelajaran kontekstual yang efektif serta mendukung strategi pedagogis berkelanjutan di pendidikan dasar.